2021
DOI: 10.3390/antiox10101562
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics of Crude Polysaccharides from 12 Selected Chinese Teas, and Their Antioxidant and Anti-Diabetic Activities

Abstract: Twelve representative edible Chinese teas (Camellia sinensis L.) from six categories (dark tea, black tea, oolong tea, white tea, yellow tea, and green tea) were selected in this study. Tea polysaccharides (TPs) were extracted with hot water, and their structural properties and biological activities, mainly antioxidant and anti-diabetic activities, were systematically evaluated. Results revealed that the extraction yields of TPs ranged from 1.81% to 6.38%, and Pu-erh tea polysaccharides had the highest extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…As the polyphenols have poor bioavailability, polysaccharides could act as a nature carrier (40). A study recent showed that the polyphenols could be the major contributor to the functionality of polysaccharides (41). Gallic acid (GA) is a primary polyphenol in dark tea, and it is known to have antihyperlipidemic effect (9).…”
Section: Discussionmentioning
confidence: 99%
“…As the polyphenols have poor bioavailability, polysaccharides could act as a nature carrier (40). A study recent showed that the polyphenols could be the major contributor to the functionality of polysaccharides (41). Gallic acid (GA) is a primary polyphenol in dark tea, and it is known to have antihyperlipidemic effect (9).…”
Section: Discussionmentioning
confidence: 99%
“…5a), the main bands of CK were noticed at 3291 cm −1 (O–H stretch) and Amide B at 2929 cm −1 (C–H bond and O–H stretch). In addition, Amide I, II and III were noticed at 1657 cm −1 (vibration of C=O stretching), 1452 cm −1 (vibration of N–H stretch and C–N deformation) and 1237 cm −1 (C–N stretching vibration and N–H deformation), respectively (Guo et al., 2021). When different exogenous additives were added to mixed shrimp surimi preparations, the broad peak of amide A was slightly changed, implying hydrogen bonds were increased between mixed shrimp surimi and exogenous additives, which may be related to the part of the molecule involved in gel formation.…”
Section: Resultsmentioning
confidence: 99%
“…The TPSs exhibited significant antioxidant and anti-diabetic (α-glucosidase inhibition and anticoagulant) activities. Particularly, Pu’er TPS had good anti-diabetic activity [ 66 ]. Wang et al found that TPSs (at high concentrations) can improve the vascular system and reduce the lipid content in diabetic patients [ 31 ].…”
Section: Bioactivitymentioning
confidence: 99%
“…Moreover, their hypoglycemic activities were concentration-dependent [ 70 ]. Guo et al evaluated the anti-diabetic activity of TPSs extracted from 12 representative edible Chinese teas ( Camellia sinensis L.) and showed that black TPSs have stronger α-glucosidase inhibitory and anti-diabetic activities than the other selected tea polysaccharides [ 66 ]. Luo et al isolated polysaccharides from guava leaves (GLPs) and showed that GLPs can significantly reduce fasting glucose, total cholesterol, total triglycerides, glycated serum protein, creatinine, and malondialdehyde in Streptozotocin-induced diabetic mice [ 71 ].…”
Section: Bioactivitymentioning
confidence: 99%